2023
DOI: 10.3390/bs13030280
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the 5Cs of Positive Youth Development to Depressive Symptoms: A Cross-Sectional Study with University Students from Peru and Spain

Abstract: Background: Prior research has documented the protective role of the 5Cs of Positive Youth Development (PYD) on adjustment problems, such as depressive symptoms. Nonetheless, more research is needed, especially in non-US contexts. The main objective of the present study was to assess associations between the 5Cs and depressive symptoms in Peru and Spain, considering gender differences across contexts. Methods: Cross-sectional data was collected from undergraduate students from Peru [n = 250] and Spain [n = 104… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…The five Cs of PYD-Competence, Connection, Confidence, Character, and Caring-are identified as such strategies. While studies show a negative correlation between the first four Cs and depression, they also reveal a positive correlation between Caring and depressive symptoms, suggesting that high empathy and emotional sensitivity may heighten vulnerability to anxiety and depression [25]. These insights emphasize the role of therapeutic interventions like ICP in cultivating internal strengths and resilience, demonstrating their alignment with PYD principles [26,27].…”
Section: Discussionmentioning
confidence: 88%
“…The five Cs of PYD-Competence, Connection, Confidence, Character, and Caring-are identified as such strategies. While studies show a negative correlation between the first four Cs and depression, they also reveal a positive correlation between Caring and depressive symptoms, suggesting that high empathy and emotional sensitivity may heighten vulnerability to anxiety and depression [25]. These insights emphasize the role of therapeutic interventions like ICP in cultivating internal strengths and resilience, demonstrating their alignment with PYD principles [26,27].…”
Section: Discussionmentioning
confidence: 88%
“…This present study aligns with the study of Conway et al [34] where confidence, connection, character, and caring had a substantial and advantageous link with thriving. The mean scores of each of the Cs seem to be low when compared to that found among youth in Peru and Spain where the highest to lowest mean range from 4.21 to 3.06 [72] while in Norway, Mesfin [73] found that the youth sampled experienced more caring, character, competence, confidence, and connection. This could imply that these Cs are present but not to their fullest in the youth sampled in this current study.…”
Section: Discussionmentioning
confidence: 97%
“…However, there is a need for caution since the majority of the participants in this current study were females. Although, it is common in previous studies that males scored higher in the 5Cs than females [10], in some studies females reported more caring and character than their male counterparts who reported more competence, confidence, and connection [37,72,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many investigations with samples from various European countries examined in their results whether men and women presented a different patterns in the development of the 5Cs. Generally, men scored higher on the dimensions of Confidence and Competence, whereas women performed likewise on Caring, Character and Connection [34,[52][53][54][55][56][57].…”
Section: Development Of the 5cs According To Gender And Identitymentioning
confidence: 93%